The case of fulminant granulomatous myocarditis. - Hritsyna, I. V. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Granulomatous myocarditis is one of the mysterious diseases: it occurs extremely rare, clinical signs and symptoms are often absent, it manifested suddenly, unexpectedly by symptoms of acute heart failure, cardiogenic shock or ventricular arrhythmia, usually finished fatally for a short period of time. The etiology and pathogenesis of this disease are unknown. Objective. The purpose of the investigation is to show the clinical course and pathological features of granulomatous myocarditis and its clinical-morphological correlations. Methods. The clinical course and anamnesis of the case were retrospectively analyzed. The data of the postmortem examination was examined in details. Results. We presented a case of idiopathic granulomatous myocarditis with fulminant onset and fatal outcome in 54-year-old man. The disease began suddenly with signs of cardiogenic shock, which was regarded as the debut of myocardial infarction. Despite the intensive care, open chest cardiac massage and artificial circulation patient died soon. Autopsy revealed extensive granulomatous myocarditis with involvement of all parts of the heart, interstitial sclerosis and left ventricle hypertrophy. Antemortal clinical signs of the disease were not observed. Conclusion. Sudden unexpected debut with hyperacute progression and rapid death in previously completely health middle-aged man are typical characteristics of this disease. Multiple foci of substitutive myocardial sclerosis are results of healed granulomas and evidences of chronic course of the disease. It remains unclear why preexisting granulomas had never manifested in the past. Extension and degree of myocardium injury does not coincide with fulminant course of the disease. The cause of the myocarditis as well as the factor which provoked exacerbation of the disease remained uncertain.